Screening and evaluation of metabolites binding PRAS40 from Erxian decoction used to treat spinal cord injury - Lin, Li; Yan, Jingchuan; Sun, Jin; Zhang, Jianfeng; Liao, Bo (Frontiers in Pharmacology, 2024)
Objective: The PRAS40 is an essential inhibitory subunit of the mTORC1 complex, which regulates autophagy. It has been suggested that Erxian Decoction (EXD) could treat spinal cord injury (SCI) via the autophagy pathway. However, the mechanism of whether EXD acts through PRAS40 remains unclear.Methods: With the help of immobilized PRAS40, isothermal titration calorimetry (ITC) and molecular docking, the bioactive metabolites in the EXD were screened. To establish in vitro SCI models, PC12 cells were exposed to hydrogen peroxide (H2O2) and then treated with the identified EXD substances. Furthermore, Western blot assay was carried out to identify potential molecular mechanisms involved. For assessing the effect of metabolites in vivo, the SCI model rats were first pretreated with or without the metabolite and then subjected to the immunohistochemistry (IHC) staining, Basso, Beattie & Bresnahan (BBB) locomotor rating scale, and H&E staining.The immobilized PRAS40 isolated indole, 4-nitrophenol, terephthalic acid, palmatine, sinapinaldehyde, and 3-chloroaniline as the potential ligands binding to PRAS40. Furthermore, the association constants of palmatine and indole as 2.84×106M-1 and 3.82×105 M-1 were elucidated via ITC due to the drug-like properties of these two metabolites. Molecular docking results also further demonstrated the mechanism of palmatine binding to PRAS40. Western blot analysis of PC12 cells demonstrated that palmatine inhibited the expression of p-mTOR by binding to PRAS40, activating the autophagic flux by markedly increasing LC3. The injection of palmatine (10μM and 20μM) indicated notably increased BBB scores in the SCI rat model. Additionally, a dose-dependent increase in LC3 was observed by IHC staining.Conclusions: This research proved that EXD comprises PRAS40 antagonists, and the identified metabolite, palmatine, could potentially treat SCI by activating the autophagic flux.